DETERMINATION OF ULTRA-LOW NB, TA, ZR AND HF CONCENTRATIONS AND THE CHONDRITIC ZR/HF AND NB/TA RATIOS BY ISOTOPE DILUTION ANALYSES WITH MULTIPLE COLLECTOR ICP-MS - Weyer S.; Münker C.; Rehkämper M.; Mezger K. (My University, 2002)
This study presents a new technique for the determination of precise and accurate concentrations of the high field strength elements (HFSE) Zr, Hf, Nb and Ta. The Ta concentration was determined for the first time by the isotope dilution (ID) technique using an isotopic tracer enriched in 180Ta. Zirconium and hafnium concentrations were also determined by ID, whereas the concentration of the mono-isotopic Nb was measured relative to Zr, after quantitative separation of the HFSE from the matrix. The analyses were performed on a Micromass Isoprobe multiple collector (MC) inductively coupled plasma source mass spectrometer (ICP-MS). Only about 0.5 ng of Zr, Hf and Ta are necessary to perform an ID analysis with an external reproducibility of better than 1% on the MC-ICP-MS using Faraday collectors. This new technique enables the precise and accurate determination of the HFSE concentrations even in ultra-depleted rocks like peridotites. The absolute uncertainties for ultra-depleted rocks, particular for Ta concentrations at the sub-ng level are limited by blanks and sample heterogeneities and not by the precision of the measurement.New and more precise Zr, Hf, Nb and Ta concentration data for the geological standard reference materials BHVO-2, BCR-2, BE-N, BIR-1 and the ultra-depleted standards PCC-1 and DTS-1 are presented. External reproducibilities of the concentration measurements are 0.4–5% for basalts and 2–10% for depleted peridotite samples (2 RSD), depending on element and concentration. The Zr/Hf and Nb/Ta ratio of the solar system was determined based on new data for two chondrites and six achondrites. The chondritic Nb/Ta of 17.6±1.0 determined in this study agrees with previous predicted values from the literature. However, the chondritic Zr/Hf of 34.2±0.3 determined in this study differs from previous literature values.